Correlation of Different Peat Soil Index Properties - Mahyan, Nur Rasfina; Taib, Siti Noor Linda; M. Sa'don, Norazzlina; Truna, Liyana; John, Jennyfer Joys (International Journal of Integrated Engineering, 2023)
The present study focuses on the physical properties of Sarawak peat soil and identifies the correlation between the index properties of peat from the present study and various locations in Malaysia. The physical properties of peat from the present study were obtained on site and in the laboratory, including degree of humification, moisture content, organic content, fibre content, specific gravity, liquid limit, linear shrinkage, and pH. The data obtained in this study and other tropical peats in Malaysia were compiled to identify their correlations. The correlation results reveal that with an increase in organic content, there is also an increase in value of moisture content, while the value of specific gravity reduces. Furthermore, as the bulk density of peat increases, the value of organic content reduces. Also, the moisture content, organic content, and fibre content of peat decrease with the increasing value of degree of humification. The correlations between different peat soil index properties have R2 values ranging from 0.75 to 0.85, showing that the peat soil index properties are consistent with findings from previous studies, in which comparable trends are found. Thus, these correlations are expected to be useful for researchers and engineers to understand the peat soil's preliminary behaviour.